Respuesta :

Answer:

-7

Step-by-step explanation:

Given the expression

4y - 2(1 - y) = -44

First expand the bracket

4y - 2 x 1 -2 x -y = -44

Negative times negative gives positive

4y - 2 + 2y = -44

Rearrange the expression

4y + 2y - 2 = -44

6y - 2 = -44

Add 2 to both sides

6y - 2 + 2 = -44 + 2

6y = -42

Divide both sides by 6

6y/6 = -42/6

y = -7

Answer:

y=-7

Step-by-step explanation:

4y-2(1-y)=-44  

4y-2+2y=-44       (-2(1-y)=-2+2y)

6y-2=-44                (Add: 4y+2y=6y)

6y-2+2=-44+2     (Add 2 in both side)

6y=-42

6y/6=-42/6               (divide 6 by both side)

y=-7